Artificial magnetic conductor with self‐complementary unit cells having very high angular stability. Issue 14 (1st July 2020) - Sarkar, S.; Gupta, B.
Abstract : This Letter presents an artificial magnetic conductor (AMC) with self‐complementary unit cells (SCUCs). The use of SCUCs results in very high angular stability of the structure; up to an incident angle of 88° for both transverse electric and transverse magnetic polarised incident waves with no shift in resonant frequency f 0 . No other structure in the literature has zero frequency shifts throughout the whole range of incident angle variations. Another interesting feature of this structure is the gradual increase of the ±90° reflection phase bandwidth with an increase in E‐field polarisation angle from φ = 0° to φ = 90° while maintaining the same f 0 . These two features make the structure unique and useful in applications where angular stability and polarisation independent f 0 are the primary concerns.